Analisis Tingkat Kematangan Gonad Ikan Gabus (Channa striata) yang Dipacu dengan Penyuntikan Gonadotropin Releasing Hormon dan Anti Dopamine (GnRH-a) Dosis Berbeda - Muhamad Noor Yasin; Irawadi Gunawan; Evander Nicharson Gultom (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2022)
Giving hormonal from outside is very helpful for successful spawning because it can accelerate the process of gonad development. This study aims to determine the effect of injection of Gonadotropin Releasing Hormone (GnRH) and anti-dopamine at different doses on the gonad maturity level (TKG), Gonado Somatic Index (GSI), and Hepato Somatic Index (HSI) of snakehead fish (Channa striata). This research was conducted for in November at the Wet Fisheries Laboratory, Department of Fisheries, Faculty of Agriculture, Palangka Raya University. The experimental design used was a completely randomized design (CRD) 4 treatments 3 replications. Treatment A dose sign (control), treatment B dose 0,3 ml/kg, treatment C 0,5 ml/kg, treatment D dose 0,7 ml/kg. The results of this study indicated that the highest gonad maturity level (TKG) was found in treatment D with a dose of 0,7 ml/kg, values TKG V. The highest gonado somatic index (GSI) value was obtained in treatment D at a dose of 0,7 ml/kg, values 2,68%. The highest Hepato Somatik Indeks (HSI) value was obtained in treatment D at a dose of 0,3 ml/kg, values 0,95% This study shows that the injection of Gonadotropin Releasing Hormone (GnRH) and anti-dopamine affects the gonad maturity level (TKG), Gonado Somatic Index (GSI), and Hepato Somatic Index (HSI) of snakehead fish (Channa striata). Keywords: GnRH-a, TKG, GSI, HSI